Design optimization analysis on the performance of BLDC motors on electric bicycles - Arifin, Zainal; Adiyasa, I. Wayan; Mohd Azri Hizami, Rasid (Institute of Physics, 2022)
Optimal design results in maximum motor performance. This type of BLDC motor has undergone design innovations such as surface-mounted permanent magnet (SPM) with variants such as: radial magnet, rectangular magnet, and bread-loaf. The position of the outer rotor is a motor design that is commonly applied to electric bicycles. The position of the magnet attached to the side of the electric motor body allows for superior torque performance. In this paper, we present an analysis of the BLDC motor on an electric bicycle that has been implemented. The motor used uses the outer rotor SPM geometry with a power of 500W. Parameter changes made are slot depth, tooth width, and comparing the basic design with the Halbach array design using 2 and 3 magnets. Changes in these parameters have an impact on power, torque, speed, and efficiency.